Competency of Teacher Educators and Student Teachers towards E-learning Tools - Gupta, Deepty; Singh, Gaurav (JOURNAL OF INDIAN EDUCATION, 2018)
Information and Communication Technology (ICT) can bring qualitative and quantitative improvement in higher education as well as in the school education system of our country. Increasing demand of E-learning has driven the Government of India to launch many new initiatives like Study Webs of Active Learning for Young Aspiring Minds (SWAYAM), e-Acharya, Shodhganga, Shodh gangotri, Open Journals Access System (OJAS), Virtual Labs, Spoken Tutorial, etc., to make the knowledge accessible to all the learners across the nation. Similarly, in the school education system, the platforms that have been created like the National Repository of Open Educational Resources (NROER), e-Pathshala, Saransh, e-Basta, Shaala Siddhi, i-Share, e-Bhasha, Shaladarpan, etc. These tools are for teachers, students and parents. All these initiatives could be successful, if the teaching-learning community is acquainted with the skills required for these. Efforts should be made to develop the skills and enhance the competencies of teachers and Teacher Educators for handling e-Learning tools. In order to study the present status, researchers have assessed the competency of Teacher Educators and student teachers towards the use of various E-learning tools. The results showed that the competencies required for using such tools was found to be lacking in the Teacher Educators and student teachers.